2019 Update of the Joint European League Against Rheumatism and European Renal Association–European Dialysis and Transplant Association (EULAR/ERA–EDTA) recommendations for the management of lupus nephritis. Issue 6 (27th March 2020) - Fanouriakis, Antonis; Kostopoulou, Myrto; Cheema, Kim; Anders, Hans-Joachim; Aringer, Martin; Bajema, Ingeborg; Boletis, John; Frangou, Eleni; Houssiau, Frederic A; Hollis, Jane; Karras, Adexandre; Marchiori, Francesca; et al.
Abstract : Objective: To update the 2012 EULAR/ERA–EDTA recommendations for the management of lupus nephritis (LN). Methods: Following the EULAR standardised operating procedures, a systematic literature review was performed. Members of a multidisciplinary Task Force voted independently on their level of agreeement with the formed statements. Results: The changes include recommendations for treatment targets, use of glucocorticoids and calcineurin inhibitors (CNIs) and management of end-stage kidney disease (ESKD). The target of therapy is complete response (proteinuria <0.5–0.7 g/24 hours with (near-)normal glomerular filtration rate) by 12 months, but this can be extended in patients with baseline nephrotic-range proteinuria. Hydroxychloroquine is recommended with regular ophthalmological monitoring. In active proliferative LN, initial (induction) treatment with mycophenolate mofetil (MMF 2–3 g/day or mycophenolic acid (MPA) at equivalent dose) or low-dose intravenous cyclophosphamide (CY; 500 mg × 6 biweekly doses), both combined with glucocorticoids (pulses of intravenous methylprednisolone, then oral prednisone 0.3–0.5 mg/kg/day) is recommended. MMF/CNI (especially tacrolimus) combination and high-dose CY are alternatives, for patients with nephrotic-range proteinuria and adverse prognostic factors. Subsequent long-term maintenance treatment with MMF or azathioprine should follow, with no or low-dose (<7.5 mg/day) glucocorticoids. The choice of agent depends on the initial regimen and plans for pregnancy. In non-responding disease, switch of induction regimens or rituximab are recommended. In pure membranous LN with nephrotic-range proteinuria or proteinuria >1 g/24 hours despite renin–angiotensin–aldosterone blockade, MMF in combination with glucocorticoids is preferred. Assessment for kidney and extra-renal disease activity, and management of comorbidities is lifelong with repeat kidney biopsy in cases of incomplete response or nephritic flares. In ESKD, transplantation is the preferred kidney replacement option with immunosuppression guided by transplant protocols and/or extra-renal manifestations. Treatment of LN in children follows the same principles as adult disease. Conclusions: We have updated the EULAR recommendations for the management of LN to facilitate homogenization of patient care.